CVD diamond film detectors for α particles with a new electrode structure of reduced graphene oxide/Au. (1st March 2019) - Zhang, Zilong; Huang, Jian; Xi, Yifan; Zhou, Xinyu; Tang, Ke; Xia, Yiben; Lu, Yicheng; Wang, Linjun
Abstract: (111)-oriented poly-crystalline diamond films (PCDs) have been deposited on Si substrates by MPCVD technology. The new electrode structure of reduced graphene oxide (RGO)/Au was successfully fabricated onto PCDs. Using the circular transmission line model (CTLM), the contact resistance of 6.6 Ω cm −2 was obtained for RGO/Au electrode on PCD surface, which was notably lower than that of 97.4 Ω cm −2 for Ti/Pt/Au electrode. Furthermore, two detectors with these two type electrodes were made respectively. The dark current, photocurrent and energy resolution of these two detectors under 5.5 MeV α particles irradiation from a 241 Am source were observed. The results demonstrated that the fabrication of RGO/Au electrode onto PCD can realize a fine ohmic contact. The photocurrent of 58.7 nA for the detector with RGO/Au electrode had higher values than that of 8.8 nA for the detector with Ti/Pt/Au electrode at the bias voltage of 100 V respectively. Due to the realization of good contact on PCD surface with RGO/Au electrode, the energy resolution of 11.9% for the detector with RGO/Au electrode better than that of 24% for the detector with Ti/Pt/Au electrode can be obtained. Fabrication of the RGO/Au electrode on PCD may provide a feasible way to improve its detection performance under α particles irradiation.